2017
DOI: 10.1139/cjfas-2016-0153
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in strontium in a tropical river: implications for otolith chemistry analyses of fish migration

Abstract: Analysis of otolith strontium isotope ratios (87Sr/86Sr) is an increasingly utilized approach for studying fish migration. We analysed surface and ground water from the Daly River catchment in the wet–dry tropics of northern Australia over 2 years. Analyses of otolith 87Sr/86Sr ratios were also conducted for freshwater sooty grunter (Hephaestus fuliginosus) and the putatively diadromous diamond mullet (Liza ordensis). Spatial variation in freshwater 87Sr/86Sr was high (range: 0.71612–0.78059), and there was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…We observed higher site specific ⁸⁷Sr/⁸⁶Sr seasonal variation than site specific ⁸⁷Sr/⁸⁶Sr year to year variation, as was also seen by Kennedy et al (2000) and Crook et al (2017). But the degree of temporal stability varied by orders of magnitude from stable to unstable across watersheds.…”
Section: Discussion and Conclusion ⁸⁷Sr/⁸⁶sr Temporal Variationsupporting
confidence: 76%
See 1 more Smart Citation
“…We observed higher site specific ⁸⁷Sr/⁸⁶Sr seasonal variation than site specific ⁸⁷Sr/⁸⁶Sr year to year variation, as was also seen by Kennedy et al (2000) and Crook et al (2017). But the degree of temporal stability varied by orders of magnitude from stable to unstable across watersheds.…”
Section: Discussion and Conclusion ⁸⁷Sr/⁸⁶sr Temporal Variationsupporting
confidence: 76%
“…The largest seasonal difference we observed was 0.00318, in French Creek. The largest seasonal difference Crook et al (2017) reported was 0.05155 on the Edith River in the wet-dry tropics of northern Australia. Crook et al (2017) suggested changes in the source water (ground vs. runoff) between the two extreme wet-dry seasons likely drove observed extreme seasonal variability.…”
Section: Discussion and Conclusion ⁸⁷Sr/⁸⁶sr Temporal Variationmentioning
confidence: 95%
“…Water 87 Sr/ 86 Sr ratio collected during the dry and wet season along an upstream gradient (water 87 Sr/ 86 Sr ratio data redrawn from Crook et al. ())…”
Section: Resultsmentioning
confidence: 99%
“…Water 87 Sr/ 86 Sr data were obtained from samples collected as a part of a separate project (Crook et al., ) along an upstream gradient from the river mouth to 405 km upstream. Samples were collected once during the wet season (eight sites, between the 5 and 13 March 2013) and once during the dry season (12 sites, between the 26 September and 7 November 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation